Strategi Guru PAI dalam Menumbuhkan Etika Lingkungan di Masa Pandemi Covid 19: Studi Kasus di Sekolah Alam Hijau Daun Mojoroto Kediri - Yusuf, Mochamad Khirzudin; M.F., Abbas Sofwan (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
PAI teachers are educators who transform their knowledge and knowledge to students with the aim that students have an Islamic spirit and behave based on Islamic values. In addition, teachers must have strategies for teaching. One of them is that teachers need to make strategies in teaching students to cultivate good environmental ethics in schools. Caring for the environment is the attitude and behaviour of trying to maintain the beauty of the environment and prevent it from being damaged. This research uses qualitative research with a case study design—data collection techniques through observation, interviews, and documentation. The results of this study found that the strategy in growing environmental ethics carried out by SAHD has succeeded in positively affecting the local community, where many small discussions and actions took place in protecting the environment.